The Improvement of Inter-Firm Linkages Within Dormant Mse Cluster: a Case of East Java - Hoetoro, Arif; Aditya Susanto, Deni; ., . (International Journal of Engineering and Technology, 2018)
The stagnant development of MSE clusters might be a priority concern of the government. It has been expected that such clusters need proper policies and regulations to well develop. In East Java, for instance, policies to improve inter-firm linkages within MSE cluster has been perceived as a vital effort to activate the dormant cluster. An effective inter-firm linkages will support the clustered MSEs to overcome their isolation problems so as to augment their productive capacity and enlarge output distribution. By taking the cluster of â€œWisata Panciâ€ in Pasuruan, East Javaâ€ as research object, this research revealed that inter-firm linkages are very beneficial for the advance development of the cluster. After suffering from financial crisis in 1998, the cluster succeeded to grow and develop to be active cluster. Methodologically, this research examined factors strengthening inter-firm linkages within the cluster by employing Analytical Hierarchy Process (AHP). In doing so, local government and cluster entrepreneurs were deeply interviewed to formulate policy choices related the strategies of inter-firm linkage improvement. The results of this research revealed that entrepreneurs within the cluster give more stressing on forward linkage improvement. Accordingly, horizontal linkage was ranked in second place. And finally, backward linkage was ranked in third place. This study concluded that both local government and entrepreneurs have same perception to more develop the cluster to be active MSEs cluster. It seems that forward linkage, especially consumptiom linkage, plays a vital role for this purpose as clustered MSEs commonly need an effective market channel to distribute their outputs widely. However, backward and horizontal linkages are also important as the linkages support further contribution to forward linkage and spur local business Â Â